A survey on the leadership among the seven urban barangay captains in the municipality of Palo, Leyte - Gabiana, Gerry G.; Tibo, Richa de los Santos (1997)
This paper is a study about the leadership patterns of the seven urban barangay captains in the locality of Palo, Leyte. These seven barangays will include Buri, Naga-Naga, Cavite East, Cavite West, Luntad, San Miguel and Sta. Cruz.